![\\ \rm\Rrightarrow f(x)=-5cos\dfrac{x}{2}+5](https://tex.z-dn.net/?f=%5C%5C%20%5Crm%5CRrightarrow%20f%28x%29%3D-5cos%5Cdfrac%7Bx%7D%7B2%7D%2B5)
Compare to standard equation of SHM
![\\ \rm\Rrightarrow y=Acos(\omega x+\phi)](https://tex.z-dn.net/?f=%5C%5C%20%5Crm%5CRrightarrow%20y%3DAcos%28%5Comega%20x%2B%5Cphi%29)
Here
![\\ \rm\Rrightarrow \omega x=\dfrac{x}{2}](https://tex.z-dn.net/?f=%5C%5C%20%5Crm%5CRrightarrow%20%5Comega%20x%3D%5Cdfrac%7Bx%7D%7B2%7D)
![\\ \rm\Rrightarrow \omega=1/2](https://tex.z-dn.net/?f=%5C%5C%20%5Crm%5CRrightarrow%20%5Comega%3D1%2F2)
Well the above one are for extra knowledge .
Solution:-
![\\ \rm\Rrightarrow 10=-5cos\dfrac{x}{2}+5](https://tex.z-dn.net/?f=%5C%5C%20%5Crm%5CRrightarrow%2010%3D-5cos%5Cdfrac%7Bx%7D%7B2%7D%2B5)
![\\ \rm\Rrightarrow 10-5=-5cos\dfrac{x}{2}](https://tex.z-dn.net/?f=%5C%5C%20%5Crm%5CRrightarrow%2010-5%3D-5cos%5Cdfrac%7Bx%7D%7B2%7D)
![\\ \rm\Rrightarrow 5=-5cos\dfrac{x}{2}](https://tex.z-dn.net/?f=%5C%5C%20%5Crm%5CRrightarrow%205%3D-5cos%5Cdfrac%7Bx%7D%7B2%7D)
![\\ \rm\Rrightarrow cos\dfrac{x}{2}=-1](https://tex.z-dn.net/?f=%5C%5C%20%5Crm%5CRrightarrow%20cos%5Cdfrac%7Bx%7D%7B2%7D%3D-1)
![\\ \rm\Rrightarrow \dfrac{x}{2}=cos^{-1}(-1)](https://tex.z-dn.net/?f=%5C%5C%20%5Crm%5CRrightarrow%20%5Cdfrac%7Bx%7D%7B2%7D%3Dcos%5E%7B-1%7D%28-1%29)
![\\ \rm\Rrightarrow \dfrac{x}{2}=\pi](https://tex.z-dn.net/?f=%5C%5C%20%5Crm%5CRrightarrow%20%5Cdfrac%7Bx%7D%7B2%7D%3D%5Cpi)
![\\ \rm\Rrightarrow x=2\pi](https://tex.z-dn.net/?f=%5C%5C%20%5Crm%5CRrightarrow%20x%3D2%5Cpi)
So.
![\\ \rm\Rrightarrow x=2\pi+2\pi n](https://tex.z-dn.net/?f=%5C%5C%20%5Crm%5CRrightarrow%20x%3D2%5Cpi%2B2%5Cpi%20n)
Answer: f(g(x)) = x - 2
<u>Step-by-step explanation:</u>
f(x) = x + 2
g(x) = x - 4
f(g(x)) = f(x - 4) = (x - 4) + 2 <em>replaced x with x - 4</em>
= x - 2 <em>simplified</em>
I need help with this question too but less hope we get a answer
Answer:
7 7/8
Step-by-step explanation: